First report of Rangelia vitalii infection (canine rangeliosis) in Argentina - Eiras, Diego Fernando (2014)
A 12-year old mixed breed neutered bitch from Misiones, Argentina, was presented with a history of fever and epistaxis. Blood, bone marrow, and lymph node samples were collected for hematology and cytology. Mild regenerative anemia was recorded and large, round, poorly stained piroplasms (> 2.5 μm) were found within erythrocytes in blood and lymph node smears. Nested PCR-RFLP on blood and bone marrow samples was positive for piroplasm DNA. The 18S rRNA gene of piroplasms was targeted. A restriction pattern of a previously unreported piroplasm was observed. The PCR product was sequenced, and the sequence obtained had 99% identity with the Rangelia vitalii sequences from Brazil when compared by BLAST analysis. Further characterization of the detected piroplasm consisted of nearly full-length sequencing (1668 bp) of the 18S rRNA gene of this organism. Those sequences were deposited in GenBank. A phylogenetic analysis indicated that they clustered together with R. vitalii from Brazil but separately from large Babesia species of dogs such as Babesia canis, and from species of Theileria of dogs as well. This is the first report of R. vitalii infection in Argentina, and the first case of canine rangeliosis diagnosed outside Brazil.